O Sentimento Religioso Na Obra Tardia De Max Horkheimer - Ramos, Luciano Sousa [UNIFESP] (2018)
This Research Proposes To Investigate The Theological Rescue In The Late Thinking Of Max Horkheimer. For This Reason, We Will Focus On The Approach To The Religious Sentiment That Occurs In The Reflections From The 1950s. However, Once We Believe There Is A Unity Of The Theme Throughout Horkheimer's Critical Theory, We Thought It Would Be Interesting To Make Specific Observations In His Other Phases Of Thinking, As In The Period Of Conception Of A Materialistic Science In The Writings Of The 1930s, And In The Reflections On Instrumental Rationality In The Central Works Of The 1940s. The Approach To The Religious Theme Inaugurates A New Stage In The Reflections Of This Author, Who Seeks Tirelessly To Sustain The Possibility Of The Existence Of An Emancipated Reason Within The Administered And Controlling Society In Almost All Aspects Of Social And Individual Life. In This Rescue Of Theological Principles, We Intend To Investigate The Continuity Of The Critical Project In Which Horkheimer Calls The Nonfulfillme